PEPC sensitization with polymethine dyes: 1. Squarylium dyes of indole row as efficient sensitizers for red region of optical spectrum - Bazhenov, M.Yu.; Golod, P.I.; Grabovskyy, V.V.; Kurdyukov, V.V.; Tolmachev, A.I.; Ilchenko, A.Ya.; Sokolov, N.I.; Zahaykevich, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Phase hologram recording is based on photoconductivity which appears in polymer molecular semiconductor film being exposed to light [1]. Photocurrent threshold depends on energy gap between valence and conduction bands of a photoconductor (PC). Energy gap of PCs based on poly-N-epoxypropylcarbazole (PEPC) which are widely used for hologram recording is rather large. That is why recording on pure PEPC film may be only in UV range of optical spectra. Thus, sensitization of PEPC with different dyes to make it sensitive to visible range is usually used for practice. Nowadays structural PEPC sensitization with fluorene electron acceptors is widely used for holographic recording material synthesis [2]. There are few publications about organic dye sensitization of PEPC due to low efficiency of first dyes used. Main obstacle to practical use of dyes like rhodamine 6G, malachite green and other 3-phenilmethans, is low diffraction efficiency (η) of hologram due to large charges thermo-relaxation in single-layer PEPC films. We have investigated some polymethine dyes like squarylium with indole residues for PEPC sensitization in red range of visible spectrum. These dyes are under intense interest due to its promising usefulness for xerography and optical recording. Particularity of such dyes is its intra-ionoide, actually bipolar, structure.